Experimental study on a self‐centering coupling beam eliminating the beam elongation effect. (9th October 2015) - Deng, Kailai; Pan, Peng; Wu, Shoujun
Summary: Traditional self‐centering coupling beams display a beam elongation effect under large shear deformation. The beam elongation effect conflicts with the rigid slab assumption and may induce harmful compressive stress between the coupling beam and the walls. This paper proposes a novel self‐centering coupling beam, aimed at eliminating the beam elongation effect. The proposed self‐centering coupling beam consists of two connecting parts and one central rocking part. The main feature of the self‐centering coupling beam is the gap between the central rocking part and the one connecting part. This gap provides sufficient space for the beam elongation effect. Friction dampers are installed at the corners of the coupling beam to provide energy dissipation capacity. An experimental study, including three specimens, was carried out. The test results demonstrate the satisfactory self‐centering and energy dissipation capacities of the novel coupling beam. Based on these test results, we quantitatively discuss the pretension force in the pretensioning strands, the friction force of the damper and the gap width in the coupling beam. A finite element analysis is performed, showing that the coupling beam gap protects the coupling beam and adjacent shear wall from damage caused by the beam elongation effect. Copyright © 2015 John Wiley & Sons, Ltd.